Media Tipografi sebagai Inovasi Pembelajaran untuk Meningkatkan Kemampuan Pramembaca Anak - Istin Anti; Andi Nurwati; Sitti Rahmawati Talango (Bunayya: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2026)
Pre-reading ability is a fundamental literacy skill that requires early stimulation to prepare children for formal education. However, many children struggle with letter recognition due to conventional and less interactive learning methods. This study aims to improve the pre-reading abilities of Group A children at PPAUDIT Lukmanul Hakim, Gorontalo Regency, through the use of typography media. This research employs a quantitative approach using Classroom Action Research (PTK) based on the Kemmis and McTaggart model, conducted in two cycles involving 19 children (9 boys and 10 girls). Data were collected through observation, documentation, and learning outcome assessments, and analyzed using descriptive percentages. The results indicate a significant improvement in children's pre-reading skills, including letter recognition (A-Z), distinguishing similar letter shapes, and matching letters with pictures. The percentage of children achieving the expected developmental criteria increased from 37.53% in the pre-cycle (low category) to 61.97% in Cycle I (fairly developed), and reached 88.81% in Cycle II (developing very well). The use of typography media provides rich visual and interactive stimulation that aligns with the concrete operational characteristics of early childhood. This study concludes that typography media is highly effective in enhancing early literacy skills. This research offers educators an innovative, visually engaging, and interactive alternative media to overcome literacy challenges in early childhood education.